The use of different types of comments in the study of "Linguistic analysis of the literary text" by foreign communicants - Budnik Anzhela; Bosak Nina (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2021)
The article considers the theoretical foundations for perceiving and understanding a work of art by foreign (non-native) speakers, outlines the types of comments that are actively implemented during the processing of literary texts at philological faculties by foreign communicators within the educational environment. It is proved that when studying the Russian language at the Faculty of Philology of Ushynsky University, foreigners encounter a number of obscure facts that are not related to the boundaries of vocabulary, grammar, phonetics or stylistics, but rather to extralinguistic spheres: social, domestic or historical. Thus, the thesis regarding the inseparability of foreign language learning from acquaintance with the culture of the country the language of which is studied, its history, religion, socio-cultural traditions, features of the national worldview of the native people is generally recognised in linguodidactics. The main purpose of such training is the need to form linguistic competence and ensure communicative competence in the acts of intercultural communication through adequate perception of the interlocutor's language and understanding of original works. It is substantiated that the perception of works of art is achieved by special comments for foreign communicants. These linguistic comments are one of the main means of forming linguistic competence.